Metabotropic Glutamate Receptors at Ribbon Synapses in the Retina and Cochlea - Klotz-Weigand, Lisa; Enz, Ralf (Cells, 2022)
Our senses define our view of the world. They allow us to adapt to environmental stimuli and are essential for communication and social behaviour. For most humans, seeing and hearing are central senses for their daily life. Our eyes and ears respond to an extraordinary broad range of stimuli covering about 12 log units of light intensity or acoustic power, respectively. The cellular basis is represented by sensory cells (photoreceptors in the retina and inner hair cells in the cochlea) that convert sensory inputs into electrical signals. Photoreceptors and inner hair cells have devel-oped a specific pre-synaptic structure, termed synaptic ribbon, that is decorated with numerous vesicles filled with the excitatory neurotransmitter glutamate. At these ribbon synapses, glutama-tergic signal transduction is guided by distinct sets of metabotropic glutamate receptors (mGluRs). MGluRs belong to group II and III of the receptor classification can inhibit neuronal activity, thus protecting neurons from overstimulation and subsequent degeneration. Consequently, dysfunction of mGluRs is associated with vision and hearing disorders. In this review, we introduce the principle characteristics of ribbon synapses and describe group II and III mGluRs in these fascinating structures in the retina and cochlea.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Bipolar cell; Cochlea; Dimerization; Inner hair cell; Metabotropic glutamate receptor; Photoreceptor; Protein interaction; Retina; Ribbon synapse; Short linear motif